The Fantastic hole: towards a theorisation of the fantastic transgression as a phenomenon of space - Patricia García (Universitat Autònoma de Barcelona, 2013)
This article develops a theoretical foundation for a type of fantastic transgression that occurs due to the incursion of an impossible spatial element within a realistic frame shared by narrator and reader. A variety of 19th, 20th and 21st century short stories and short films are examined to establish a theoretical outline for this transgressive phenomenon, here denominated «the fantastic as a phenomenon of space», or «the fantastic of space». Three categories of this phenomenon are proposed: the transgressions of the «body» and the notion of being (physically and existentially) in space, of the «boundary» and the principles of definition and circumscription, and «hierarchy», related to the dialogue between container and contained. Ultimately, these three categories meet within one single motif: the fantastic hole, presented as a paradigmatic spatial distortion of the fantastic as a phenomenon of space.